Scenario Seismic Hazard Analysis of the Mataram “Fault”: An Initial Study of Geophysical Approach - Yuanita Andikasari Lian; Jaya Syahbana Arifan; Damayanti Cahya; Tri Atmojo Hasan; Zalbuin Mase Lindung; Faris Fikri (BIO Web of Conferences)
Indonesia, as a country in the Ring of Fire, has negative impacts in terms of tectonic and volcanic hazards. As an example of an area frequently hit by earthquakes, One of the area in the country frequently hit by earthquakes is the Special Region of Yogyakarta (DIY). Based on the latest studies, a new source has been discovered, which is the east-west trending “fault” called the Mataram or Tambakboyo “Fault”. This “fault” is still in the initial phase of research. This study aims to provide additional information on the Mataram “Fault” from a geophysical point of view, namely by using the gravimetric method. This method provides an understanding of the existence of a fault, namely the indication of a clear contrast difference (order of km) so that the geometry of the Mataram “fault” can be obtained. This parameter will be used in earthquake hazard modeling by using OpenQuake software. It is hoped that with this research, the geometric characteristics of the Mataram “Fault” and the earthquake hazard can be obtained.